Lead us not into temptation: The seven deadly sins as a taxonomy of temptations. Issue 10 (14th September 2018) - Burkley, Edward; Burkley, Melissa; Curtis, Jessica; Hatvany, Thomas
Abstract: People constantly experience a tug‐of‐war between their self‐control on one end and their temptations on the other. Although a great deal of research has examined such self‐control dilemmas, much of it has focused on the "push" of self‐control rather than the "pull" of temptations. To facilitate future work on this latter construct, we sought to create a taxonomy of temptations. Using a top‐down approach, we relied on the philosophical and historical concept of the seven deadly sins—gluttony, greed, lust, sloth, envy, pride, and wrath—to identify and define the most commonly experienced temptations. In support of this taxonomy, we review evidence for the role that self‐control plays in resisting each of these seven temptation domains, including work on trait self‐control and momentary exertions of self‐control. Where applicable, we identify areas where research is lacking and make suggestions for future work. Lastly, we discuss how this taxonomy offers researchers both theoretical and practical benefits.